Obstructed obturator hernia containing Meckel’s diverticulum: a case report - Jain, Sharad; Maida, Motilal; Patil, Sagar Manohar (International Surgery Journal, 2018)
An obturator hernia is a rare type of hernia and unusual cause of acute intestinal obstruction. The combination of diagnostic difficulty and high mortality rates make obturator hernia a serious diagnosis that can be potentially overlooked. We present a case of an elderly multiparous woman presented at the emergency room with complaints of abdominal distension, pain, vomiting and constipation for the last 4 days. On examination abdominal tenderness with distension was noted. Hernial orifices were normal. A CT and MRI reports were suggestive of right obstructed obturator hernia. Patient underwent emergency exploratory laparotomy. The hernial sac contained a narrow neck Meckel’s diverticulum with perforation of proximal ileum. Resection of perforated segment along with Meckel’s diverticulum was done and end to end ileo-ileal anastomosis was performed. Obturator foramen was closed with simple polypropylene sutures. CT/MRI scan is of immense help in preoperative diagnosis. Once the diagnosis is suspected or confirmed, patient should be taken for surgery as early as possible.